Quadrature Multiplexed Structured Illumination Imaging - Chengyang Hu; Sigang Yang; Minghua Chen; Hongwei Chen (IEEE Photonics Journal)
Higher dimensional optical imaging has seen remarkable growth in the past decade. As a representative method, multiplexed structured illumination (MSI) has been widely introduced for its ultra-high resolution of high-dimensional information. In this letter, an imaging framework for recovering higher dimensional image data, which terms quadrature multiplexed structured illumination (QMSI), is proposed and demonstrated. QMSI incorporates the illumination pattern spatial phase information as a new parameter into the encoding process. This strategy can double the frequency spectrum utilization without any overhead compared to MSI, which means it can double the image sequence depth or image spatial resolution. As a proof of concept, we demonstrate the performance of QMSI by experiments on multispectral imaging.